The indigenous intelligentsia and its role in the cultural and linguistic revitalization of its peoples - Meneses Tutaya, Norma (2013)
The presence of an indigenous intelligentzia (Andean and Amazonian) with evolution in rural and urban contexts that consciously interacts for their community development is discussed here. This intelligentzia join the tradition kept in the community ancient wises and the modernization exhibit by indigenous professionals and indigenous businessmen. Nevertheless, both parts of this indigenous intelligentzia, the traditional and modern, display many contradictions in its social activity, specially those from the urban sectors who usually and urgently are involved in acculturation and “language moving” processes. Even though these obstacles, today this indigenous intelligentzia is assuming its sociocultural and political leadership among their pairs and in front of the Peruvian official society. Their activity, consciously and growingly, is realized in pro of the cultural and linguistic revitalizations of their people, besides the most urgent aspects like the defense of its territory, its human and citizen rights.